IMPLEMENTING THE TAKE AND GIVE METHOD TO ENHANCE ENGLISH VOCABULARY AMONG STUDENTS - Maesyarah, Ummul; Muliati, A.; Ariyani, Amra (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study aims to determine whether or not the Take and Give method in enhances English vocabulary among students at SMPS DDI Mattoanging, Bantaeng. Employing a quantitative research approach, the investigation uses a pre-experimental design involving pre-test and post-test evaluations to measure the development of students' vocabulary proficiency. The results indicate a significant improvement, with the average score rising from 49.48 in the pre-test to 86.43 in the post-test. A paired sample t-test was conducted and produced a t-score of 9.728 with a p-value of 0.000, confirming a statistically significant difference between the two sets of scores. Additionally, the normalized gain (N-Gain) analysis yielded an average of 0.6931, suggesting that most students achieved considerable progress. These findings confirm that the Take and Give method is a successful approach for boosting students’ English vocabulary skills.